The Political Scar of Epidemics - Barry Eichengreen; Orkun Saka; Cevat Giray Aksoy (Center for Economic Studies and Ifo Institute (CESifo), 2021)
What political legacy is bequeathed by national health crises such as epidemics? We show that epidemic exposure in an individual's “impressionable years” (ages 18 to 25) has a persistent negative effect on confidence in political institutions and leaders. The effect is specific to the impressionable ages, observed only for political institutions and leaders, and does not carry over to other institutions and individuals with one key exception. That exception is strong negative effects on confidence in public health systems, suggesting that the loss of confidence in political institutions and leaders is associated with the (in)effectiveness of a government's healthcare-related responses to past epidemics. We document this mechanism, showing that weak governments took longer to introduce policy interventions in response to the COVID-19 outbreak, and demonstrating that the loss of political trust is larger for individuals who experienced epidemics under weak governments. Finally, we report evidence suggesting that the epidemic-induced loss of political trust may discourage electoral participation in the long term.
Keywords: D72; F50; I19; 330; epidemics; trust; political approval